Application of Conservative Power Theory to load and line characterization and revenue metering - Paredes, Helmo K. M. [UNESP]; Marafao, Fernando P. [UNESP]; Mattavelli, Paolo; Tenti, Paolo (Institute of Electrical and Electronics Engineers (IEEE), 2012)
This paper proposes a set of performance factors for load characterization and revenue metering. They are based on the Conservative Power Theory, and each of them relates to a specific load non-ideality (unbalance, reactivity, distortion). The performance factors are capable to characterize the load under different operating conditions, considering also the effect of non-negligible line impedances and supply voltage deterioration. © 2012 IEEE.
Keywords: Line impedance; Load characterization; Nonideality; Operating condition; Performance factors; Power theory; Specific loads; Supply voltages; Commerce